Benefits and drawbacks of using multiple shrinkage mitigating strategies on performance of fiber-reinforced mortar. (October 2022) - Aghaee, Kamran; Khayat, Kamal H.
Abstract: Shrinkage mitigating strategies have been successfully used to prevent concrete cracking. Numerous studies have demonstrated the efficiency of shrinkage mitigating materials (SMM), such as expansive agent (EA), shrinkage reducing admixture (SRA), and superabsorbent polymer (SAP) on reducing shrinkage and cracking; however, few studies have addressed the limitations of using these materials. In addition, the mechanism of negative effect on microstructure and mechanical properties when these materials are used at high contents or in combinations is not well defined. This study investigates the effect of CaO-based EA, SRA, and SAP on compressive strength development, fiber pull-out strength, and shrinkage of fiber-reinforced mortar (FRM) mixtures. Hydration kinetics and internal relative humidity are also determined. Advanced microstructural characterization techniques are employed to explore the mechanism underlying the effect of SMM on the mechanical properties and shrinkage of FRM mixtures. Test results indicate that FRM made with coupled systems of SMM limited to 5% EA, 1% SRA, and 0.25% SAP are preferred. The preferred SMM combination considering compressive strength, fiber pull-out strength, and shrinkage is the coupled system made of EA and SRA. High heat of hydration obtained using 10% EA results in excessive portlandite formation and high expansion, which adversely affects the mechanical properties. The use of 0.5% SAP with additional internal curing water contributes to the excessive expansion of SAP particles and creation of voids into the matrix, which reduce compressive strength and fiber-matrix bonding. The results revealed that the individual use of 7.5% EA and coupled use of 5% EA either with 0.5% SRA or 0.125% SAP can result in producing flowable, high strength, and low shrinkage FRM mixtures applicable to repair.